Extreme Desire for Motherhood: Analysis of Narratives From Women Undergoing Assisted Reproductive Technology (ART) - Viviana Langher; Fabiola Fedele; Andrea Caputo; Francesco Marchini; Cesare Aragona (Europe's Journal of Psychology, 2019)
The problem of infertility and its consequent treatment (denoted as Assisted Reproductive Technology or ART) represent an increasing phenomenon, especially in industrialized countries. Confronting with one’s own procreative limitations can generate strong negative emotional reactions. This study aims at understanding how the desire for motherhood manifests itself in infertile women undergoing ART, studying their emotional and subjective perspective. An in-depth explorative research study was conducted on 17 infertile women attending an Italian hospital clinic for fertility treatment. Emotional text analysis was conducted to analyze the corpus of their interviews, allowing the identification of four thematic domains (clusters) which refer, respectively, to the following emotional dimensions: an inclination to self-sacrifice, seen as the price to be paid for the desired success of the treatment (Cluster 1), pursuit of inclusion in the world of procreative mothers (Cluster 2), precarious equilibrium between the deep desire for a baby and the withdrawal from the treatment (Cluster 3), surrender to any possible consequence in order to obtain the desired mother-child relationship (Cluster 4). The witness of the couples’ suffering for their condition of infertility and their strong desire for parenting can represent a source of high pressure for the fertility care staff, as they are the only ones responsible for the fulfillment of the great dream of biological parenthood. For these reasons, a multidisciplinary approach, which involves psychological as well as medical experts all working together, could benefit both the patients and the healthcare professionals and improve the quality of the reproductive healthcare services.